Empowerment of MSMEs in Caringin Sub-District, Bogor in the Management and Preparation of Financial Statements - Rusmanah, Enok; Hary Suryantoro; Dewi Atika; Mutiara Raras; Ira Rima Anita (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Micro, Small, and Medium Enterprises support the Indonesian economy. However, they are still experiencing obstacles in developing their businesses and access to capital from financial institutions. Similar to the condition, MSMEs in the Caringin Sub-district, have several problems due to a lack of comprehensive knowledge of financial management, inadequate management infrastructure, and less skill in preparing transparent and accountable financial statements. Therefore, community service is carried out to provide additional insight and skills by empowering them with financial management knowledge and preparation of financial statements skills for MSMEs. This service collaborates with the IKM MSMEs forum which organized more than 300 MSMEs in Caringin District, Bogor Regency. The empowerment consisted of socialization, knowledge sharing, and mentoring. As a result, MSME players were very enthusiastic about participating and taking advantage of this activity to consult on the obstacles and practices faced by their businesses. According to the feedback, 80% of the participants acknowledged gaining new insight and skills. These results also highlight the importance of empowerment in providing transparent and accountable financial management and reporting, which can speed up the MSME development.